SURFACE CHARGE DEVELOPMENT ON TRANSITION METAL SULFIDES: AN ELECTROKINETIC STUDY - AN ELECTROKINETIC STUDY - Bebie J.; Schoonen M.A.A.; Fuhrmann M.; Strongin D.R. (My University, 1998)
The isoelectric points, pHi.e.p., of ZnS, PbS, CuFeS2, FeS, FeS2, NiS2, CoS2, and MnS2 in NaCl supported electrolyte solutions are estimated to be between pH 3.3 and 0.6, with most of the isoelectric points below pH 2. The first electrokinetic measurements on NiS2, CoS2, and MnS2 are reported here. Below pHi.e.p. the metal-sulfide surfaces are positively charged, above pHi.e.p. the surfaces are negatively charged. The addition of Me2+ ions shifts the pHi.e.p. and changes the pH dependence considerably. The isoelectric points of the measured transition metal sulfides in the absence of metal ions or dissolved sulfide (H2S or HS-) are in agreement with those found in earlier studies. The pH range of observed isoelectric points for metal sulfides (0.6-3.3) is compared to the considerably wider pHi.e.p. range (2-12) found for oxides. The correlation between pHi.e.p. and the electronegativities of the metal sulfides suggests that all metal sulfides will have an isoelectric point between pH 0.6 and 3.3. Compared to metal oxides, sulfides exhibit an isoelectric point that is largely independent of the nature of the metal cation in the solid.